The ECB and the Quest for Competitiveness of the Eurozone: From the Competitive Devaluation of the Euro to QE. Issue 4 (4th July 2017) - Talani, Leila Simona
Abstract: That the lack of competitiveness of EU member states in the wake of the globalization era was a problem from the start of EMU is clear from the various interventions on this issue by the European institutions. These started from the White Paper on Growth, Competitiveness and Employment, of 1993, up to the various versions of the Lisbon agenda and agenda 2020. It might even be possible to hypothesize, in line with Colin Crouch and the literature on the political economy of competitiveness, that the establishment of EMU was an attempt to regain some of the competitiveness lost with the advent of the era of globalization. Accordingly, the role of the ECB to save the Eurozone dominant socio-economic sectors has been divided into two phases. In the first phase, the strategy was to rely on the depreciation of the euro vis-à-vis the dollar, which indeed gave some results in the first years of life of the European currency. With respect to the present phase, it is undeniable that the burden of the costs of the global financial crisis fell on the weakest countries of the system, through the two related phenomena of the sovereign debt crisis and the ensuing austerity programmes.